ELEMENTS WHICH TRIGGER EMPLOYEE'S INTENTION TO DISCLOSE FRAUD VIA A WHISTLEBLOWING SYSTEM: A CASE STUDY - Anggraini, Putri; Putra, Ramadhan Nugraha (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2018)
Fraud is very liquid; thus, it could occur both in public sector and private institutions. The consequences of fraud could be very damaging such as the loss of assets and the ruin of a company's reputation. BPK as one of the governmental institutions in Indonesia is obliged to implement a whistleblowing system as a means to detect any fraudulent activities. It is believed that an effective whistleblowing system is likely to be credible and secure so that all employees could disclose misconducts without any hesitation. Therefore, this study aims to contribute to the novelty of the whistleblowing system which has been implemented in BPK. There are several elements to be considered in setting up a whistleblowing system namely, secrecy of the tipsters' identity, incentives, whistleblowers' protection, accessibility, training of ethical program, power owned by the addressee, the perpetrators and the potential whistleblowers, management's support as well as their response to the tips given by the employees. A questionnaire and descriptive statistical analysis are used to rank the elements from the most important to the least essential items in a whistleblowing system from the perspective of the employees in BPK. The result shows that BPK's employees consider the whistleblowers' protection as the most critical element in the system; whereas, rewards is the least factor which triggers them to blow the whistle. Those elements, however, are integral parts which complement each other in establishing an effective whistleblowing mechanism.